PELAKSANAAN PEMBELAJARAN IPA BAGI ANAK TUNARUNGU - Jean Jua Herlianti (Universitas Negeri Padang, 2015)
Abstract : The research is begin from implementation of saints subject in SLB YPPLB Padang. Generally, when studying saints subject many media can be used as conveys of material what the want to inform, that time employing of media or the helping of instrument its be less to used with the result child when implementation of saints subject being unattractive and the desirability of child to knowing that material cant visible on saints subject. With knowing why child with deaf in SLB YPPLB Padang especially on the class VI who less pay attentions teachers when conveying saints subject, so researcher doing research to make formula this problem that is how implementations of saints subject for child with deaf class VI on SLB YPPLB padang. Keyword: Pelaksanaan Pembelajaran IPA, Anak Tunarungu